Identifikasi cefixime pada bakteri di perairan pesisir Kota Manado - Elisa Yohana Anjali Wulur; Ronald I. Ottay; Zwingly Christian Porajow; Henry Malcom Frank Palandeng (UNIVERSITAS SAM RATULANGI, 2021)
Background: The presence of antibiotics in the bodies of water could potentially have negative impacts on health. The release of antibiotics into the environment might cause the emergence of bacteria strains that are more resistant to antibiotics. This study aimed to identify the potential presence of cefixime in the coastal water of Manado City.Methods: This study was a susceptibility testing towards seawater sample isolated bacteria. This study used Kirby-Bauer disc diffusion methods.Results: All isolates showed resistance to cefixime. We identified four isolates: Acinetobacter spp, Staphylococcus spp, Bacillus spp, and Pseudomonas spp.Conclusion: The resistant isolates indicate the presence of cefixime in the coastal waters of Manado.Keywords: Cefixime, resistance, antibiotic susceptibility testing, seawater, Manado City.